THE IMPACT OF MARKETING MIX ON FARMERS’ PURCHASING DECISIONS FOR POTATO SEEDS AT PD. NUGRAHA PUTRA - Daniel Juan Panca Sinaga; Lies Sulistyowati (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2025)
PD. Nugraha Putra has a high level of potato seed production; however, its sales volume has not yet matched its production output, thus creating a gap between production and sales. Thus, product, price, place, and promotion aspects are marketing mix factors that influence farmers' decisions. The purpose of this study was to examine the impact of these factors on potato purchasing decisions from PD. Nugraha Putra. The method used for the assessment was quantitative, using survey techniques. Primary data were obtained from 50 user surveys conducted by PD. Nugraha Putra using a convenience sampling methodology. The data were analyzed descriptively and then followed by linear regression using SPSS software. This study showed that two variables—product, price, location, and promotion—had a significant influence on respondents' purchasing decisions, both simultaneously and partially.